Comparative study of volatile and non-volatile flavor substances in squid from multiple origins - Mengli Han; Xin Jiang; Meijiao Gui; Qianqian Liang; Yuan Gu; Xin Song; Wenzheng Shi (Food Chemistry: X)
This study compared and analyzed the similarities and differences in odor and taste between Japanese flying squid and Equatorial, Indian Ocean, and Peruvian squid. Headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) and headspace solid-phase microextraction gas chromatography–mass spectrometry (HS-SPME-GC–MS), respectively, identified 52 and 43 volatile compounds, with aldehydes and alcohols being the main volatile substances. Cluster analyses showed that Equatorial squid were closest in odor to Japanese flying squid. A total of 16 free amino acids, 6 flavor nucleotides and 3 organic acids were identified from the four squid species by HPLC. There was no significant difference between Japanese flying squid and Peruvian squid in umami intensity. Hierarchical cluster analysis classified the flavors of the four squids into three categories, that was Equatorial squid and Japanese flying squid, Indian Ocean squid, Peruvian squid, which will provide a reference for raw material substitution of Japanese flying squid.